2018
DOI: 10.1021/acsenergylett.8b01588
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Engineering Improves Efficiency of Lead-Free Tin-Based Hybrid Perovskite Solar Cells beyond 9%

Abstract: Here, we report on the effect of different antisolvent dripping on film morphology and charge recombination of mixed formamidinium–methylammonium tin iodide (FA0.75MA0.25SnI3) as a light absorber in perovskite solar cells. N,N-dimethyl methanamide (DMF) and dimethyl sulfoxide (DMSO) were used as the mixed solvent in the perovskite precursors together with tin fluoride (SnF2) as an additive. Diethyl ether (DE), toluene (TL), and chlorobenzene (CB) were employed as antisolvents for comparison. Our results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
191
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(205 citation statements)
references
References 52 publications
(94 reference statements)
1
191
0
Order By: Relevance
“…Although it is known that 2D tin‐halide perovskites are oxygen sensitive, it has also been shown that they are more stable towards oxygen and humidity than their 3D homologous . Today, the best PCE for a 2D tin halide perovskite is 5.94 %, which is comparable to the first 2D PSC reported and no too far from the best lead‐free 3D PSC (9.06 %) …”
Section: Lead‐free 2d Perovskites In Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that 2D tin‐halide perovskites are oxygen sensitive, it has also been shown that they are more stable towards oxygen and humidity than their 3D homologous . Today, the best PCE for a 2D tin halide perovskite is 5.94 %, which is comparable to the first 2D PSC reported and no too far from the best lead‐free 3D PSC (9.06 %) …”
Section: Lead‐free 2d Perovskites In Solar Cellsmentioning
confidence: 99%
“…[106,108] Today,t he best PCE for a2 Dt in halide perovskite is 5.94 %, which is comparable to the first 2D PSC reported [88] and no too far from the best lead-free 3D PSC (9.06 %). [109] Other attempts to replace lead were 2D copper halide-based perovskites. The first report was by Cortecchia et al, [110] who reported the use of MA 2 CuBr 4Àx Cl x -type materials in solar cell devices ( Figure 11).…”
Section: Lead-free 2d Perovskites In Solar Cellsmentioning
confidence: 99%
“…Although the Pb halide perovskites still hold the supreme position regarding materials and device characteristics and performance, Sn halide perovskites have also benefited in numerous ways from the partial or complete substitution of Pb with Sn. Sn halide perovskites are adaptable to various preparation techniques which may include solution and vapor deposition methods . These techniques usually follow a low temperature processing pathway.…”
Section: Merits and Challenges Of Sn Halide Perovskitesmentioning
confidence: 99%
“…Up till now, both the commercial and the homemade SnI 2 have been used for high‐efficiency Sn‐based PSCs. However, homemade SnI 2 is not accessible for all the researchers for lack of either equipment or synthetic skills.…”
Section: Strategies For High Performancementioning
confidence: 99%